Adenoid Hypertrophy in Adults: An Underdiagnosed Entity? - Ishwar Singh; Avani Jain; Purodha Prasad; Pragya Rajpurohit (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Adenoid enlargement is uncommon in adults. We studied the varied presentation of adenoid hypertrophy in two adults. A 45 year old male who presented with nasal obstruction and snoring, and a 35 year old male who presented with non resolving chronic otitis media. In both the patients, adenoid hypertrophy was diagnosed by nasal endoscopy and confirmed by CT scan. Adenoidectomy in these patients resulted in symptomatic improvement. Therefore, adenoid hypertrophy should also be considered as a cause or contributing factor in nasal obstruction and related pathologies in adults.